2010
DOI: 10.1098/rspb.2010.0587
|View full text |Cite
|
Sign up to set email alerts
|

Atypical gaze patterns in children and adults with autism spectrum disorders dissociated from developmental changes in gaze behaviour

Abstract: Eye tracking has been used to investigate gaze behaviours in individuals with autism spectrum disorder (ASD). However, traditional analysis has yet to find behavioural characteristics shared by both children and adults with ASD. To distinguish core ASD gaze behaviours from those that change with development, we examined temporo-spatial gaze patterns in children and adults with and without ASD while they viewed video clips. We summarized the gaze patterns of 104 participants using multidimensional scaling so th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
217
5
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 226 publications
(276 citation statements)
references
References 20 publications
(60 reference statements)
26
217
5
2
Order By: Relevance
“…The nature of this finding is different to the reduced attention to faces often observed in children with autism (e.g. Klin et al 2002;Nakano et al, 2010;Riby & Hancock, 2008), but is in-line with recent findings that observed no overall reduction in eye-region viewing in older, high functioning individuals with autism when only one face or person was present in the each visual stimulus (Fletcher-Watson et al 2009;Freeth et al 2010). Findings from this new cohort of participants replicated previous findings, from Freeth et al (2013a) and Laidlaw et al (2011), using equipment enabling a much more finegrained temporal and spatial analysis of eye-movements compared to these previous studies and indicate that individuals with more autistic traits are focussing on socially relevant areas within their visual field as much as individuals who show fewer autistic traits, providing the opportunity to effectively spot and process any subtle social cues that may be produced by the social partner.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…The nature of this finding is different to the reduced attention to faces often observed in children with autism (e.g. Klin et al 2002;Nakano et al, 2010;Riby & Hancock, 2008), but is in-line with recent findings that observed no overall reduction in eye-region viewing in older, high functioning individuals with autism when only one face or person was present in the each visual stimulus (Fletcher-Watson et al 2009;Freeth et al 2010). Findings from this new cohort of participants replicated previous findings, from Freeth et al (2013a) and Laidlaw et al (2011), using equipment enabling a much more finegrained temporal and spatial analysis of eye-movements compared to these previous studies and indicate that individuals with more autistic traits are focussing on socially relevant areas within their visual field as much as individuals who show fewer autistic traits, providing the opportunity to effectively spot and process any subtle social cues that may be produced by the social partner.…”
Section: Discussioncontrasting
confidence: 83%
“…Children with ASD are often found to look less to other people's faces compared to typically developing children, the eye region in particular (Klin et al, 2002;Nakano et al, 2010;Riby & Hancock, 2008). Some adult studies have also reported reduced looking to the eyes in individuals with ASD (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Hosozawa, Tanaka, Shimizu, Nakano and Kitazawa (2012) and Nakano et al (2010) have made this comparison between autism and SLI by comparing gaze data to the same dynamic social stimuli across two studies. The first study (Nakano et al, 2010) involved children and adults with autism and typical controls, and the second (Hosozawa et al, 2012).…”
Section: Cross Syndrome Comparison -Specific Language Impairmentmentioning
confidence: 99%
“…The first study (Nakano et al, 2010) involved children and adults with autism and typical controls, and the second (Hosozawa et al, 2012). involved children with SLI and typical controls.…”
Section: Cross Syndrome Comparison -Specific Language Impairmentmentioning
confidence: 99%
See 1 more Smart Citation